Failure of d-cycloserine to reverse cognitive disruption induced by scopolamine or phencyclidine in primates. - Rupniak, N; Duchnowski, M; Tye, S; Cook, G; Iversen, S (1992)
The partial glycine agonist d-cycloserine may be of therapeutic use as a cognitive enhancer. We examined the ability of d-cycloserine (3-14 mg/kg i.m.) to reverse cognitive impairments induced by scopolamine (0.03 mg/kg) or PCP (0.25 mg/kg). There was no evidence for a dose-related improvement in visuospatial memory using retention intervals of 2,10 or 20 sec. A possible explanation for these findings is that central glycine function cannot be adequately increased using systemic administration of d-cycloserine in this dose range.